Gross Anatomical Studies on the Vertebral Column of Indian Mongoose (Herpestes javanicus) - Ankem, Prasanth Babu; Ramayya, P. Jagapathi; Rao, S. Dhilleswara; Gopireddy, Madhavi; Singh, Tomar M.P. (Indian Journal of Veterinary Anatomy, 2018)
Indian mongoose (Herpestes javanicus) is a small predatory mammal capable of surviving in a variety of habits including deserts, forests, agricultural and urban areas. Vertebral formula of the Indian mongoose is C7, T13, L7, S3Cy21-25.The transverse processes of 3rd to 5thcervical vertebrae were bifid and showed anterior and posterior processes whereas trifid in 6thvertebra. At the root of the transverse processes of 2nd to 6th cervical vertebrae showed foramen transversarium. In thoracic vertebrae capitular facets of adjacent vertebrae together formcapitular cavities for heads of the ribs. Dorsal spinous processes were upward and backward in direction upto 10th thoracic vertebra,whereas the spine of 11th vertebra was vertical, and considered as â€œanticlinal vertebraâ€. The transverse processes were small and less developed.The anterior articular processes of lumbar vertebrae were well developed and strongly curved medially. Posterior articular processes were projected laterally and their articular areas were facing laterally. Mamillary processes were present in first four lumbar vertebrae and the accessory processes were present in first 6 lumbar vertebrae except the 7th lumbar vertebra. The sacrum was formed by the fusion of three vertebrae. On the dorsal surface on either side of the articular processes two intervertebral foraminawere present. The pelvic surface was deeply concave and showed two ventral sacral foramina. The first sevencoccygeal vertebrae were typical vertebrae but beyond the seventh they were atypical vertebrae. The ventral surface of the bodies of 7th to 10th caudal vertebrae showed â€˜Vâ€™ or â€˜Yâ€™ shaped haemalarches.